Growth Of Mustard Greens (Brassica Rapa L.) Due To The Application Of Urea Fertilizer With Various Biuret Contents - Sugesti, Rahmawita (Journal of Science Innovare, 2023)
This research was conducted in Cikampek, Karawang Regency. The purpose of this study was to study the effect of various doses of nitrogen fertilizer on the growth and yield of mustard greens. This study was arranged in a randomized block design consisting of 7 doses of urea, namely: control (without fertilizer); 50 kg/ha; 100 kg/ha; 150 kg/ha; 200 kg/ha; 250 kg/ha and 300 kg/ha, each treatment was repeated three times so that there were 21 experimental units. The results showed that the administration of urea fertilizer had a very significant effect on the growth and yield of mustard greens (plant height, number of leaves, fresh weight and dry weight of plants) and the best dose of urea fertilizer could be achieved at a dose of 200 kg/ha.